2015
DOI: 10.1148/radiol.14141414
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoprogression in Patients with Glioblastoma: Assessment by Using Volume-weighted Voxel-based Multiparametric Clustering of MR Imaging Data in an Independent Test Set

Abstract: VVMC is a superior and more reproducible imaging biomarker than single-parameter measurements for differentiating between pseudoprogression and ETP in patients with glioblastoma. Online supplemental material is available for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Seventeen studies evaluated DSC, [13][14][15]17,18,20,[23][24][25][27][28][29][30][31]34,36,39 8 evaluated DCE, 16,19,21,22,32,37,38,40 and 3 evaluated both DSC and DCE. 26,33,35 There were a total of 937 cases (54%) of tumor progression and 806 cases (46%) of treatment change. Investigators reported that pseudoprogression was the specific treatment effect under evaluation in 13 studies, 14,17,18,[29][30][31]33,34,[36][37][38][39][40] radiation necrosis in 4 studies, 15,16,19,21 and both in 2 studies.…”
Section: Selection Of Studies and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen studies evaluated DSC, [13][14][15]17,18,20,[23][24][25][27][28][29][30][31]34,36,39 8 evaluated DCE, 16,19,21,22,32,37,38,40 and 3 evaluated both DSC and DCE. 26,33,35 There were a total of 937 cases (54%) of tumor progression and 806 cases (46%) of treatment change. Investigators reported that pseudoprogression was the specific treatment effect under evaluation in 13 studies, 14,17,18,[29][30][31]33,34,[36][37][38][39][40] radiation necrosis in 4 studies, 15,16,19,21 and both in 2 studies.…”
Section: Selection Of Studies and Study Characteristicsmentioning
confidence: 99%
“…26,33,35 There were a total of 937 cases (54%) of tumor progression and 806 cases (46%) of treatment change. Investigators reported that pseudoprogression was the specific treatment effect under evaluation in 13 studies, 14,17,18,[29][30][31]33,34,[36][37][38][39][40] radiation necrosis in 4 studies, 15,16,19,21 and both in 2 studies. 25,34 Patients meeting inclusion criteria for pseudoprogression developed a new lesion during concurrent radiation and chemotherapy 29 out to 6 months after treatment completion.…”
Section: Selection Of Studies and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dynamic contrast-enhanced mri parameters have been particularly useful in conjunction with parameters derived from dsc-mri. Multiparametric analysis from both dsc-mri and dynamic contrast-enhanced mri was used in a study of 108 patients, successfully discriminating pseudoprogression from true progression with a sensitivity of 87% and a specificity of 87.1%-90.3% 56 .…”
Section: Perfusion Imagingmentioning
confidence: 99%